Thermally exfoliated graphene oxide reinforced fluorinated pentablock poly(l‐lactide‐co‐ε‐caprolactone) electrospun scaffolds: Insight into antimicrobial activity and biodegradation. Issue 22 (27th February 2016) - Okan, Burcu Saner; Marset, Azucena; Seyyed Monfared Zanjani, Jamal; Sut, Pınar Akkus; Sen, Ozlem; Çulha, Mustafa; Menceloglu, Yusuf
ABSTRACT: Three‐dimensional fluorinated pentablock poly(l ‐lactide‐ co ‐ε‐caprolactone)‐based scaffolds were successfully produced by the incorporation of thermally exfoliated graphene oxide (TEGO) as an antimicrobial agent with an electrospinning technique. In a ring‐opening polymerization, the fluorinated groups in the middle of polymer backbone were attached with a perfluorinated reactive stabilizer having oxygen‐carrying ability. The fiber diameter and its morphologies were optimized through changes in TEGO amount, voltage, polymer concentration, and solvent type to obtain an ideal scaffold structure. Instead of the widely used graphene oxide synthesized by Hummer's method, TEGO sheets having a low amount of oxygen produced by thermal expansion were integrated into the fiber structure to investigate the effect of the oxygen functional groups of TEGO sheets on the degradation and antimicrobial activity of the scaffolds. There was no antimicrobial activity in TEGO‐reinforced scaffolds in the in vitro tests in contrast to the literature. This study confirmed that a low number of oxygen functional groups on the surface of TEGO restricted the antimicrobial activity of the fabricated composite scaffolds. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43490. Abstract :